Incisional hernia formation in hepatobiliary surgery using transverse and hybrid incisions: a systematic review and meta-analysis - Davey, S (Ann R Coll Surg Engl, 2020)
INTRODUCTION: Evidence suggests that midline incisions should be closed with the small-bite technique to reduce IH formation. No recommendations exist for the closure of transverse incisions used in hepatobiliary surgery. This work systematically summarises rates of IH formation and associated technical factors for these transverse incisions. METHODS: A systematic search was undertaken. Studies describing the incidence of IH were included. Incisions were classified as transverse (two incision types) or hybrid (transverse with midline extension, comprising five incision types). The primary outcome measure was the pooled proportion of IH. Subgroup analysis based on minimum follow-up of two years and a priori definition of IH with clinical and radiological diagnosis was undertaken. FINDINGS: Thirteen studies were identified and included 5,427 patients; 1,427 patients (26.3%) underwent surgery for benign conditions, 3,465 (63.8%) for malignancy and 535 (9.9%) for conditions that were not stated or classified as ‘other’. The pooled incidence of IH was 6.0% (2.0–10.0%) at a weighted mean follow-up of 17.5 months in the transverse group, compared with 15.0% (11.0–19.0%) at a weighted mean follow-up of 42.0 months in the hybrid group (p = 0.045). Subgroup analysis did not demonstrate a statistical difference in IH formation between the hybrid versus transverse groups. CONCLUSION: Owing to the limitations in study design and heterogeneity, there is limited evidence to guide incision choice and methods of closure in hepatopancreatobiliary surgery. There is an urgent need for a high-quality prospective cohort study to understand the techniques used and their outcomes, to inform future research.